2019
DOI: 10.1038/s41598-019-39577-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a single session of chiropractic care on strength, cortical drive, and spinal excitability in stroke patients

Abstract: The objective of this study was to investigate whether a single session of chiropractic care could increase strength in weak plantar flexor muscles in chronic stroke patients. Maximum voluntary contractions (strength) of the plantar flexors, soleus evoked V-waves (cortical drive), and H-reflexes were recorded in 12 chronic stroke patients, with plantar flexor muscle weakness, using a randomized controlled crossover design. Outcomes were assessed pre and post a chiropractic care intervention and a passive movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 45 publications
5
58
0
2
Order By: Relevance
“…The increase observed in the present study may reflect an improvement in early sensorimotor function that is related to the observed increase in strength found in a recent study of chronic stroke survivors after a single session of chiropractic spinal manipulation [41]. In that study [41], Holt et al investigated the effect of chiropractic spinal manipulation on motor recovery in a chronic stroke population and found that, on average, plantarflexion muscle strength increased by approximately 64% after a single session of chiropractic care.…”
Section: Sepssupporting
confidence: 74%
See 2 more Smart Citations
“…The increase observed in the present study may reflect an improvement in early sensorimotor function that is related to the observed increase in strength found in a recent study of chronic stroke survivors after a single session of chiropractic spinal manipulation [41]. In that study [41], Holt et al investigated the effect of chiropractic spinal manipulation on motor recovery in a chronic stroke population and found that, on average, plantarflexion muscle strength increased by approximately 64% after a single session of chiropractic care.…”
Section: Sepssupporting
confidence: 74%
“…It is, therefore, interesting that the chiropractic intervention showed an increase in the N30 SEP peak amplitude, considering previous studies in subclinical subjects have consistently reported a decrease in N30 SEP peak amplitude after chiropractic spinal manipulation [32,36,39,40]. The increase observed in the present study may reflect an improvement in early sensorimotor function that is related to the observed increase in strength found in a recent study of chronic stroke survivors after a single session of chiropractic spinal manipulation [41]. In that study [41], Holt et al investigated the effect of chiropractic spinal manipulation on motor recovery in a chronic stroke population and found that, on average, plantarflexion muscle strength increased by approximately 64% after a single session of chiropractic care.…”
Section: Sepssupporting
confidence: 73%
See 1 more Smart Citation
“…The prevailing thought on the neurophysiological impact of spinal/extremity manipulation is one of perceptual attunement brought about by mechanisms related to greater afferentation by peripheral receptors [28][29][30]; however, our consistent interaction effects suggest the modulation of visual perception may also be a possibility. Furthermore, the action capabilities of the participant are likely promoted by enhanced neural drive through supraspinal, spinal or extremity-based mechanisms [20,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that SM alters mechanoreceptive input from the spine and that this in turn alters the way in which the brain processes, interprets, and integrates other interoceptive and exteroceptive information [ 5 ]. Previous studies have investigated the effect of SM on the function of the nervous system at different levels, for example motor output, sensory processing, functional performance, and sensorimotor integration [ 5 , 15 , 16 ]. These studies have contributed to the hypothesized model, described by Haavik and Murphy [ 5 ], which proposes potential mechanisms to explain how SM may alter bodily and CNS function [ 5 ].…”
Section: Introductionmentioning
confidence: 99%